2017
DOI: 10.1371/journal.pone.0186411
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific expression at the androgen receptor alpha gene in a hybrid unisexual fish, the Amazon molly (Poecilia formosa)

Abstract: The all-female Amazon molly (Poecilia formosa) is the result of a hybridization of the Atlantic molly (P. mexicana) and the sailfin molly (P. latipinna) approximately 120,000 years ago. As a gynogenetic species, P. formosa needs to copulate with heterospecific males including males from one of its bisexual ancestral species. However, the sperm only triggers embryogenesis of the diploid eggs. The genetic information of the sperm donor typically will not contribute to the next generation of P. formosa. Hence, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…All-female Amazon molly was generated by distant hybridization of the Atlantic molly ( Poecilia mexicana ) and the sailfin molly ( Poecilia latipinna ). The ASE analysis of androgen receptor α suggested a maternal bias in ovary from Amazon molly (Zhu et al, 2017a). There were high ratios of maternal homolog expression of transcripts in diploid and tetraploid hybrids of Carassius auratus red var.…”
Section: Discussionmentioning
confidence: 99%
“…All-female Amazon molly was generated by distant hybridization of the Atlantic molly ( Poecilia mexicana ) and the sailfin molly ( Poecilia latipinna ). The ASE analysis of androgen receptor α suggested a maternal bias in ovary from Amazon molly (Zhu et al, 2017a). There were high ratios of maternal homolog expression of transcripts in diploid and tetraploid hybrids of Carassius auratus red var.…”
Section: Discussionmentioning
confidence: 99%
“…Here, meiosis and recombination are maintained (e.g., in whiptail lizards, [ 87 ]). In contrast, our ameiotic species lacks recombination and is hence a ‘frozen hybrid’ at all nuclear loci [ 18 , 33 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, analysis of allele-specific expression (ASE) revealed that scarb1 was detected in both RCC (85.7% for scarb1a-A and 14.3% for scarb1a-B ; 12.5% for scarb1b-A and 87.5% for scarb1b-B ) and 4nRR (76.9% for scarb1a-A , 73.3% for scarb1b-A , and 60% for scarb1c-A ). ASE, often driven by cis-regulatory elements, is a common event in various animal species, including humans, mice, chickens, Amazon mollies, California tiger salamanders, and hybrid tilapias ( Cooper & Shaffer, 2021 ; Lagarrigue et al, 2013 ; Lo et al, 2003 ; Song et al, 2012b ; Zhou et al, 2019 ; Zhu et al, 2017 ; Zhuo et al, 2017 ). These occurrences have been linked to disease risk and phenotypic severity of disease-causing CDS variants.…”
Section: Discussionmentioning
confidence: 99%